2014
DOI: 10.1016/j.bjoms.2014.01.018
|View full text |Cite
|
Sign up to set email alerts
|

Salvage operations for patients with persistent or recurrent cancer of the maxillary sinus after superselective intra-arterial infusion of cisplatin with concurrent radiotherapy

Abstract: The purpose of our study was to evaluate the feasibility of salvage surgery for patients with persistent or recurrent maxillary sinus cancer after superselective intra-arterial cisplatin infusion with concomitant radiotherapy (RADPLAT). We retrospectively analyzed 61 patients with maxillary sinus cancer who underwent RADPLAT.Chemotherapy comprised 100-120 mg/m 2 superselective intra-arterial cisplatin administered at a median rate of four times weekly. Concurrent radiation therapy was administered at a median … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 17 publications
0
9
0
Order By: Relevance
“…The salvage treatment protocol at our institution may have contributed to the improvement in survival. Although there is limited literature regarding salvage treatment for patients with progression or recurrence (22), 5 of the 25 patients who had locoregional recurrence achieved locoregional control with salvage treatment in our study.…”
Section: Discussionmentioning
confidence: 79%
“…The salvage treatment protocol at our institution may have contributed to the improvement in survival. Although there is limited literature regarding salvage treatment for patients with progression or recurrence (22), 5 of the 25 patients who had locoregional recurrence achieved locoregional control with salvage treatment in our study.…”
Section: Discussionmentioning
confidence: 79%
“…A large number of clinical studies have confirmed that salvage surgery or repeated radiotherapy could be chosen as the local treatment of relapse in these patients [ 4 , 5 ]. However, functional and cosmetic outcomes after surgical treatment for patients with advanced recurrent tumors are far from satisfactory [ 11 ]. The complication rate of salvage surgery after intensive chemoradiotherapy for patients with head and neck cancer has been reported to be 11-63% [ 12 ].…”
Section: Discussionmentioning
confidence: 99%
“…Sakashita et al . [ 11 ] reported that 18% of patients with recurrent cancer of the maxillary sinus developed serious operative complications after salvage surgery. An observational study by Iwata et al .…”
Section: Discussionmentioning
confidence: 99%
“…Advances in treatment methods such as a combination of surgery, chemotherapy and radiotherapy have led to improved local control of primary lesions such as sinonasal cavity or pharynx squamous cell carcinomas (SCCs). 1 3 However, patients may develop distant metastasis after treatment, even if the primary lesion was successfully controlled. 4 In addition, systematic screening by whole-body scanning using CT or 18 F-fluorodeoxyglucose (FDG) positron-emission tomography (PET)/CT at short intervals can be used to detect distant metastases in HNSCC patients after the curative treatment, but this may not be cost-effective.…”
Section: Introductionmentioning
confidence: 99%